Peanut oral immunotherapy transiently expands circulating Ara h 2–specific B cells with a homologous repertoire in unrelated subjects - Patil, Sarita U.; Ogunniyi, Adebola O.; Calatroni, Agustin; Tadigotla, Vasisht R.; Ruiter, Bert; Ma, Alex; Moon, James; Love, J. Christopher; Shreffler, Wayne G. (Journal of allergy and clinical immunology, 2015)
Peanut oral immunotherapy (PNOIT) induces persistent tolerance to peanut in a subset of patients and induces specific antibodies that might play a role in clinical protection. However, the contribution of induced antibody clones to clinical tolerance in PNOIT is unknown. We hypothesized that PNOIT induces a clonal, allergen-specific B-cell response that could serve as a surrogate for clinical outcomes. We used a fluorescent Ara h 2 multimer for affinity selection of Ara h 2–specific B cells and subsequent single-cell immunoglobulin amplification. The diversity of related clones was evaluated by means of next-generation sequencing of immunoglobulin heavy chains from circulating memory B cells with 2x250 paired-end sequencing on the Illumina MiSeq platform. Expression of class-switched antibodies from Ara h 2–positive cells confirms enrichment for Ara h 2 specificity. PNOIT induces an early and transient expansion of circulating Ara h 2–specific memory B cells that peaks at week 7. Ara h 2–specific sequences from memory cells have rates of nonsilent mutations consistent with affinity maturation. The repertoire of Ara h 2–specific antibodies is oligoclonal. Next-generation sequencing–based repertoire analysis of circulating memory B cells reveals evidence for convergent selection of related sequences in 3 unrelated subjects, suggesting the presence of similar Ara h 2–specific B-cell clones. Using a novel affinity selection approach to identify antigen-specific B cells, we demonstrate that the early PNOIT-induced Ara h 2–specific B-cell receptor repertoire is oligoclonal and somatically hypermutated and shares similar clonal groups among unrelated subjects consistent with convergent selection.